Extended metaphor in Adrienne Rich's poem: Diving into the wreck - Putri, Aulia; Siahaan, Safnidar (CAHAYA PENDIDIKAN, 2024)
In her poignant poem "Diving into the Wreck," Adrienne Rich masterfully navigates the intricate landscape of self-discovery, unraveling the layers of personal history and confronting the formidable obstacles inherent in the quest for truth. Rich employs a nuanced blend of thematic elements and literary devices to construct an evocative extended metaphor, skillfully guiding readers through the profound exploration of diving into a wreck. The study delves into the intricate tapestry woven by Rich, shedding light on the poet's deliberate choices and the profound impact of this metaphorical journey on the overall interpretation of the poem. By immersing readers in the depths of the extended metaphor, Rich invites them to reflect on the complexities of identity, the tumultuous journey through life, and the transformative process of plumbing one's personal depths. Through this rich and imaginative exploration, the poem resonates as a timeless testament to the universal human experience of self-discovery.